Possible Involvement of Standardized Bacopa monniera Extract (CDRI-08) in Epigenetic Regulation of reelin and Brain-Derived Neurotrophic Factor to Enhance Memory - Preethi, Jayakumar; Singh, Hemant K.; Rajan, Koilmani E. (Frontiers in Pharmacology, 2016)
Bacopa monniera extract (CDRI-08; BME) has been known to improve learning and memory, and understanding the molecular mechanisms may help to know its specificity. We investigated whether the BME treatment alters the methylation status of reelin and brain-derived neurotropic factor (BDNF) to enhance the memory through the interaction of N-methyl-D-aspartate receptor (NMDAR) with synaptic proteins. Rat pups were subjected to novel object recognition test following daily oral administration of BME (80 mg/kg) in 0.5% gum acacia (per-orally,p.o.; PND 15-29)/ three doses of 5-Azacytidine (5-azaC; 3.2 mg/kg) in 0.9% saline (intraperitoneally, i.p.) on PND-30. After the behavioural test, methylation status of reelin, BDNF and activation of NMDAR, and its interactions with synaptic proteins were tested. Rat pups treated with BME/ 5-azaC showed higher discrimination towards novel objects than with old objects during testing. Further, we observed an elevated level of unmethylated DNA in reelin and BDNF promoter region. Up-regulated reelin along with the splice variant of apolipoprotein E receptor 2 (ApoER 2, ex 19) form a cluster and activate NMDAR through disabled adopter protein-1 (DAB1) to enhance BDNF. Observed results suggest that BME regulate reelin epigenetically, which might enhance NMDAR interactions with synaptic proteins and induction of BDNF. These changes may be linked with improved novel object recognition memory.